Design and development of dialysate temperature control module prototype for hemodialysis - Abdul Jabbar, Mohamed Haroon (2019)
In the last few decades, complications caused during hemodialysis (HD) treatment remain a significant cause of morbidity and mortality in patients. During standard HD, there is a significant tendency for the body temperature to rise slightly, which is sufficient to cause complications. Recent studies show that the controlling of body temperature by altering the dialysate temperature, can reduce the complication episodes. Although the importance of active regulation of dialysate temperature control and its benefits have mentioned in literature, an enhanced design of controller and its comparison with dated commercial controller -Blood Temperature Monitor (BTM) have not been reported yet.